2000
DOI: 10.1046/j.1525-1438.2000.010003212.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in young women with endometrial carcinoma: a report of 20 cases and review of literature

Abstract: We retrospectively reviewed the pathologic features of patients with endometrial carcinoma (EC) treated in our facility between 1989 and 1998. First, we identified the clincopathologic features of young women with EC and compared them with similar patients from the literature. Second, 148 EC patients were divided into two groups: group A (age45, n = 128). The mean follow-up periods were 65 months and 50 months in groups A and B, respectively. Group A patients had better disease-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 37 publications
4
21
0
1
Order By: Relevance
“…Several studies have shown an association of aneuploidy with poor prognosis (49,50), while the expression of steroid receptors is associated with higher survival rates and better treatment response (51). Among oncogenes, the overexpression of HER-2 is associated with a reduced survival rate, but the clinical meaning and the predictability of treatment response are not fully understood (52).…”
Section: Biomarkers For Prognosis and Treatmentmentioning
confidence: 99%
“…Several studies have shown an association of aneuploidy with poor prognosis (49,50), while the expression of steroid receptors is associated with higher survival rates and better treatment response (51). Among oncogenes, the overexpression of HER-2 is associated with a reduced survival rate, but the clinical meaning and the predictability of treatment response are not fully understood (52).…”
Section: Biomarkers For Prognosis and Treatmentmentioning
confidence: 99%
“…5 % der Fälle treten vor dem 40. Lebensjahr auf [91]. Das klinische Hauptsymptom ist die postmenopausale bzw.…”
Section: Introductionunclassified
“…There is a significantly higher portion of the disease confined to the inner half of the myometrium (p < 0.004). Patients less than 45 years of age were shown to have a better disease-free survival than older patients (p < 0.028) 16 .…”
Section: Primary Treatment With Progestins In Endometrial Cancer Patimentioning
confidence: 97%